Unconscious Spirituality: Toward a Contemporary Conceptualization - Jastrzębski, Andrzej (Journal of religion and health, 2022)
Until now, the concept of unconscious spirituality has not received sufficient academic attention. Despite the fact that it surfaces now and then in various psychotherapeutic theories and clinical practice, it lacks appropriate conceptualization. The aim of this article is to address this issue. We shall begin with a short presentation of the history and complexity of the concept of unconscious spirituality. Subsequently, we will discuss at some length the theories of James and Jung, to then focus on the much less explored work of Victor Frankl. Lastly, we will turn to some contemporary clinical theories and conclude with a proposal for defining unconscious spirituality as an unperceived connection with the sacred, especially as a connection with one’s true self or spiritual core. We hope that this will be a meaningful contribution to developing a more inclusive and universal conceptualization of unconscious spirituality.